Comparative Metabolomic Analysis of Three Medicinal Paphiopedilum Species Reveals Divergence in Antioxidant Capacity and Functional Compound Profiles - Jinhan Sang; Yishan Yang; Kanghua Xian; Jiang Su; Jianmin Tang; Chuanming Fu; Fengluan Tang; Xiao Wei (Molecules, 2025)
This study explores the metabolite diversity and potential medicinal value of three Paphiopedilum species—P. dianthum, P. micranthum, and P. barbigerum—using widely targeted metabolomics via HPLC-MS/MS in conjunction with in vitro antioxidant assays. A total of 2201 metabolites were detected across the three species, with flavonoids emerging as the dominant class (480 compounds, accounting for 21.8% of total metabolites). Comparative metabolomic analysis showed that flavonoid levels varied most prominently among the species. Notably, the metabolic profile of P. barbigerum (PB) diverged substantially from those of P. dianthum (PD) and P. micranthum (PM), which shared a higher degree of similarity with each other. Quantitative evaluation of antioxidant-associated metabolites revealed that PB exhibited the greatest enrichment in compounds with antioxidant potential, particularly flavonoids and phenolic acids, followed by PM and PD. These results were corroborated by antioxidant assays, in which PB demonstrated the highest free radical scavenging activity, with PM and PD displaying progressively lower effects. Differences in flavonoid content likely underpin these variations in antioxidant capacity. KEGG pathway enrichment analysis indicated that differentially expressed metabolites were primarily involved in flavonoid-associated biosynthetic routes, notably flavonoid biosynthesis (ko00941) and isoflavonoid biosynthesis (ko00943), with ko00941 being the most enriched. Within this pathway, PB showed eight significantly upregulated flavonoid metabolites, while PM and PD had seven and five, respectively. The observed differences may stem from species-specific expression of key biosynthetic enzymes such as flavonoid 3′-hydroxylase (F3′H) in PM and flavonoid 3′,5′-hydroxylase (F3′5′H) in PB, which influence both flavonoid composition and antioxidant potential.